Factors affecting the students' choice of librarianship as a career - Buenrostro, Juan C.; Vallejo, Rosa M.; Miñoza, Aurora A. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1977)
This study is about the factors affecting the choice of librarianship as a career by undergraduate library science students. Two-hundred and twenty six third year and fourth year library science students were used as subjects in this study. They were purposively selected from nine library schools in Metro Manila during the first semester 1977-1978.
A constructed questionnaire entitled "A Questionnaire on the Factors Affecting the Students' Choice of Librarianship as a Career" was the instrument used for gathering the data. The questionnaire was divided into four major parts: 1) the demographic characteristics of the individuals who chose librarianship as a career; 2) the decision making for the choice of librarianship as a career; 3) factors inspiring and influencing their decisions in the choice of librarianship as a career; and 4) the motivational factors as reflected by the students' concepts of librarianship as a career.
This study revealed that students enrolled in the library schools are predominantly women. They are also young. They have good academic records in high schools. Most of the students come from Region IV. They belong to large families with an average socio-economic status.
Majority of the subjects made their decision of choosing librarianship as a career after high school. Two thirds of the subjects decided for themselves and were really determined in their choice of librarianship as their career. This was further revealed in the ranking of preferences concerning various fields of study where the subjects still preferred library science. The majority of the subjects planned to seek library jobs after graduation preferring to work in the special library with Reference as the type of work they would engage in.
The subjects were more inspired than influenced. Of the ten factors listed, five factors were highly rated by the subjects consisting of inspirational factors and influencing factors.
The most highly rated motivational factor as reflected by the students' concepts of librarianship as a career was the "service that librarianship renders to society."
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Library science as a profession